Unjuk Kerja (Performance Assessment) sebagai Bentuk Penilaian Autentik dalam Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Sekolah Dasar: Studi Literatur - Erlysta Eka Purnama; Dhika Mahendra; Sindy Puji Lestari (Prosiding Konferensi Ilmiah Dasar, 2026)
Critical thinking is a 21st-century competency that elementary students must master, yet empirical studies in Indonesia still report low-to-moderate achievement at this level, partly due to the dominance of written-test-based assessment that fails to authentically capture students' reasoning processes. This article examines the role of performance assessment as a form of authentic assessment in developing elementary students' critical thinking skills, while mapping the research gaps that remain open. The study employs a literature review method with a narrative-thematic approach toward 20 national and international journal sources published between 2015 and 2025, screened through a two-stage selection process that yielded 11 core studies for synthesis in a comparison matrix. The synthesis shows that performance assessment is consistently reported to contribute to students' interpretation, analysis, and inference indicators; however, of the six elementary-level studies found, none explicitly integrated performance assessment with critical thinking measurement within a single instrument. The article concludes that performance assessment holds strong potential for fostering critical thinking in elementary schools, although the empirical evidence remains fragmented, and therefore proposes a conceptual framework linking critical thinking indicators to performance assessment rubrics as an agenda for further development.